Dryland Grain Sorghum in North Central Kansas - Warmann, Gerald W.; Dhuyvetter, Kevin C. (My University, 1995)
This publication provides estimated cost and returns for forward farm planning for dryland grain sorghum in north central Kansas.
MF2159_1995_10
Keywords: MF2159; Crops; Economics; MF